Perceived Teacher Informal Relationship Scale: A scale development and measurement invariance study - Demirtaş, Zülfü; Çaçan, Hanifi; Uslukaya, Alper (Asya Publishing and Consultancy, 2023)
This work is intended to develop a measuring tool for determining teacher perception of informal relationships. The pool of items created by researchers through a literature review has been presented with expert assessment of the validity of the content, face, and meaning, and a draft scale has been created by making necessary revisions to the feedback. The draft form was applied to 214 teachers working in the central districts of Diyarbakır, exploratory factor analysis was made on the obtained data set, and a six-dimensional scale structure consisting of 20 items was determined. In order to verify this structure, data were collected from 306 teachers working in the central districts of Diyarbakir, and the six-factor scale structure was confirmed based on the goodness of fit values estimated by confirmatory factor analysis. In addition, AVE (Average Variance Extracted), the root of AVE, composite reliability, and correlation among factors were checked, and it was seen that the scale provided the convergent and discriminant validity conditions as a result of the values reached. For reliability analysis, Cronbach's Alpha coefficients and composite reliability values were checked together, and it was seen that the scale had sufficient reliability values. The measurement invariance of the scale was tested according to the categories of gender (female-male), marital status (married-single), level of employment (primary school, secondary school, and high school), and seniority (1-10 years, 11-20 years, 21 and above), and the formality of the scale, metric, scalar, and strict invariance conditions were found to satisfy. Consequently, it was concluded that the scale in question is a valid and reliable scale that can be used to measure teacher perception of informal relationships. © 2023, Asya Publishing and Consultancy. All rights reserved.
Keywords: Factorization; Formal relationship; Informal relationship; Measurement invariance; Scale development